1999
DOI: 10.1103/physreve.60.145
|View full text |Cite
|
Sign up to set email alerts
|

Exact solutions of some urn models of relaxation in glassy dynamics

Abstract: We consider two simple models, called "urn models," for a general N-ball, M-urn problem. These models find applications in the study of relaxation in glassy dynamics. We obtain exact analytical results in these two cases for the average relaxation time tau to reach the ground state. In model I we also obtain the functional dependence of tau for large N, and in model II we obtain an asymptotic (N-->infinity) dependence of tau as a function of the number of urns M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…∼ k log k − k, giving a logarithmic correction on a semi-log plot. For larger values of k, a different approach is needed; however, Arora et al [19] showed that for k = N the asymptotic result is τ FP N ∼ V N , which coincides with the asymptotic behavior of our result when we put V = N/ρ. Comparison between mean-field and spatial cases.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…∼ k log k − k, giving a logarithmic correction on a semi-log plot. For larger values of k, a different approach is needed; however, Arora et al [19] showed that for k = N the asymptotic result is τ FP N ∼ V N , which coincides with the asymptotic behavior of our result when we put V = N/ρ. Comparison between mean-field and spatial cases.…”
supporting
confidence: 88%
“…Since diffusive processes give rise to spatial and temporal correlations that render the problem analytically intractable, we also consider a mean-field version of this problem, in which particles can jump not only between neighbouring sites, but to any of the sites in the system with equal probability, which reduces the problem to a type of Ehrenfest urn model [13,19]. We show numerically that this approximation provides a qualitative explanation of the behaviour of the mean first-passage time also for diffusive dynamics.…”
mentioning
confidence: 99%
“…Relaxation times to reach the ground state at T = 0 do of course diverge with the system size (as 2 N for the Backgammon model [156,157,161], or more slowly as N 2 [161] in variants such as model C from [151]), but at T > 0 the final energy per box or particle lies above the ground state by a finite amount and so all timescales remain finite.…”
Section: Relaxation Timescales and Dynamical Transitionsmentioning
confidence: 99%
“…Let us consider a system quenched down to T = 0 and the aging regime reached in the asymptotic long-time regime where (dE/dt)/E << 1. In that limit, the system has a number of empty boxes N empty = −E and further decrease of that number by one unit ∆E = −1 requires a time that exceedingly grows as E decreases toward its minimum value E = −N + 1 (all particles condensed into a single box) [197,198]. Therefore, as relaxation slows down, for a long time the system wanders through the constant energy surface by exchanging particles among occupied boxes.…”
Section: The Backgammon and Urn Modelsmentioning
confidence: 99%